The effect of homogeneous catalyst for the degradation of sodium dodecylbenzene sulfonate in water by means of ultrasonic irradiation - Abu Hassan, Mohd. Ariffin; Mohd. Yunus, Rosli; Khamis, Aidee Kamal (Universiti Teknologi Malaysia, 2006)
Linear Alkylbenzene Sulfonate (LAS) is a major anionic surfactant used widely in industrial detergents and the production of household products throughout the world because of its effectiveness. Its presence in wastewaters may cause environmental concern. Ultrasound has proven to be a very useful tool in enhancing the reaction rates in a variety of reacting systems. Additionally, it has successfully increased and enhanced the removal and destruction of volatile compounds in aqueous solution. The aim of this research is to study the treatment of synthetic aqueous solutions containing a commercial Linear Alkylbenzene Sulfonate (LAS), namely Sodium Dodecylbenzene Sulfonate (SDBS), by means of ultrasound irradiation. The possibility of coupling ultrasound with a suitable oxidation catalyst to improve treatment efficiency will also be investigated. HPLC, TOC, COD and pH analyses will be carried out to investigate the effect of degradation of SDBS. In this research, SDBS degradation with three different treatments (US alone, US with H2O2and US with Fenton reagent) was investigated. All treatment presented in this research were performed in triplicate by using sonication bath at 30 Â°C, 40 kHz , 500 W and sonication time of 120 min. From the discussion, by using the US + Fenton treatment appears to be the highest in terms of % TOC removal which is 67% and followed by the others two treatment which is US + H2O2 and US alone treatment have been achieved at 55% and 12%. It was found that the main degradation of SDBS proceeds via a reaction with OH radicals and since SDBS is anionic surfactant of negligible volatility. The initial degradation rate (d[SDBS]/dt, within the first 30 min) increases by using the US + Fenton treatment which is 0.68 M/min followed by US + H2O2 and US alone were achieved at 0.52 M/min and 0.44 M/min respectively.